Site‐specific weed management—constraints and opportunities for the weed research community: Insights from a workshop. (28th February 2021) - Lati, Ran Nisim; Rasmussen, Jesper; Andujar, Dionisio; Dorado, Jose; Berge, Therese W.; Wellhausen, Christina; Pflanz, Michael; Nordmeyer, Henning; Schirrmann, Michael; Eizenberg, Hanan; Neve, Paul; Jørgensen, Rasmus Nyholm; et al.
Abstract: The adoption of site‐specific weed management (SSWM) technologies by farmers is not aligned with the scientific achievements in this field. While scientists have demonstrated significant success in real‐time weed identification, phenotyping and accurate weed mapping by using various sensors and platforms, the integration by farmers of SSWM and weed phenotyping tools into weed management protocols is limited. This gap was therefore a central topic of discussion at the most recent workshop of the SSWM Working Group arranged by the European Weed Research Society (EWRS). This insight paper aims to summarise the presentations and discussions of some of the workshop panels and to highlight different aspects of weed identification and spray application that were thought to hinder SSWM adoption. It also aims to share views and thoughts regarding steps that can be taken to facilitate future implementation of SSWM.